The Plight of Informal Settlers and the Value of People’s Participation in Implementing Housing Projects - San Gabriel, Hilda (Social Sciences and Development Review, 2012)
The research undertaken served as an imperative material as it looks into the circumstance of lack of housing of urban poor people and how these people struggle amidst their condition, its a bottom-up approach development initiative, and it documents people’s voices and sentiments, and how conflict was resolved. Specifically, it focuses on social capital formation in the context of establishing organizations such as cooperatives and peoples organizations that would address the need of the community: the basic need for shelter. In the process of building the housing projects, the research looks at how people’s participation, cultural background becomes critical for both the effectiveness and sustainability of the project.